Notes on Eopsis beaumonti Benson 1959 (Hymenoptera, Tenthredinidae). - Beneš, Karel (Contributions to Entomology = Beiträge zur Entomologie, 2015)
The distribution, life history and larva of Eopsis beaumonti Benson 1959 are briefly described. The larva is extremely adapted to endophagous life. It is monophagous on Bistorta major and is unique in having large terminal spiracles on the subanal plate of the tenth abdominal segment.Keywordsdistribution, larva, food plant, adaptation.